Effects of toroidal transition on ultimate bearing capacity of submarine cone-cone connection structures - JING Teng; WU Fan; ZHANG Er; ZHANG Yuchen (Zhongguo Jianchuan Yanjiu, 2020)
[Objectives] The influence of the toroidal transition on the ultimate load-carrying capacity of ribbed cone-cone connections is studied by finite element methed.[Methods] The arc length method is used to calculate the ultimate load-carrying capacity of cone-toroid-cone and cone-cone connections without initial geometric imperfections and with initial imperfections of first-order modal deformation respectively. The failure modes are then analyzed. Through a comparison,the influence of the toroidal transition on the ultimate load-carrying capacity of cone-cone connections at different conical angles is obtained.[Results] The results show that when the cone angle on one side of the large radius is small,the failure of cone-toroid-cone and cone-cone structures occurs in the cone shell plate on the other side of the small radius. The ultimate bearing capacity of the cone-toroid-cone structure is better than that of the cone-cone structure. The ultimate bearing capacity of the cone-toroid-cone structure with initial geometric imperfections of modal deformation decreases by 12%-13% compared with that without initial geometric imperfection. Then,with the increase of the cone angle on one side of the large radius,the difference between the ultimate bearing capacity of the two structures decrease gradually. When the cone angle continues to increase,the damage area of the structure becomes a cone shell on the other side of the large radius. The ultimate bearing capacity of the cone structure is consistent with that of the cone-cone structure,the ultimate bearing capacity of cone-toroid-cone structures with initial imperfections of modal deformation decreases by about 8.8% compared with those without initial geometric imperfections, and the sensitivity of the cone-toroid-cone structure to the initial imperfections of the small radius cone shell is higher than that of the large radius cone shell.[Conclusions] The results of this research can provide references for the design of cone-toroid-cone connection structures for submarines.